Impact of broad-spectrum anthelmintic treatment in the summer on the weight gain of reindeer calves - Oksanen, A.; Soveri, T.; Nieminen, M. (Rangifer, 1996)
The results indicate that broad-spectrum helminth control may increase summer growth of reindeer calves at least when heavily parasitized. The significant weight gain caused by the treatment was, however, relatively small. On natural reindeer pastures with seasonal migration the parasite infection pressure is possibly considerably lower than in this trial.